Interplay Between Primary Cilia, Ubiquitin-Proteasome System and Autophagy - Avalos-Carrasco, y (Elsevier B.V., 2019)
Cilia are microtubule-based organelles located at the cell surface of many eukaryotic cell types. Cilia control different cellular functions ranging from motility (for motile cilia) to signal transduction pathways (for primary cilia). A variety of signaling pathways are coordinated by this organelle during development, cell migration and cell differentiation. Interestingly, aberrant ciliogenesis or altered cilium signaling has been associated with human diseases, notably in cancer. Disruption of cilia through mutation of genes encoding cilia proteins has been also linked to multiple human disorders referred as ciliopathies. Recent studies highlight the interplay between cilia and proteostasis. Here we review findings regarding the crosstalk between cilia and two proteolytic systems, the ubiquitin proteasome system and the autophagy-lysosomal system and discuss the potential implications in human disease including ciliopathies. © 2019 Elsevier B.V. and Société Française de Biochimie et Biologie Moléculaire (SFBBM)